Fungi detected in trunk of stone fruits in the Czech Republic - Pečenka, Jakub; Peňázová, Eliška; Tekielska, Dorota; Ondrášek, Ivo; Nečas, Tomáš; Eichmeier, Aleš (Acta Agraria Debreceniensis, 2019)
This study was focused on detection of the spectrum of fungi in the wood of stone fruits using molecular genetic methods. Samples were obtained from apricots, plums and sweet cherry trees from region of Moravia, one sample was obtained from Myjava (Slovakia). Segments of symptomatic wood were obtained from dying stone fruit trees with very significant symptoms. This study describes detection of the fungi in the wood of 11 trees in general in 5 localities. The cultivation of the fungi from symptomatic wood and sequencing of ITS was carried out. Eleven fungal genera were determined in the stone fruits wood, particularly Irpex lacteus, Fomes fomentarius, Neofabraea corticola, Calosphaeria pulchella, Cytospora leucostoma, Phellinus tuberculosus, Stereum hirsutum, Collophora sp., Pithomyces chartarum, Aureobasidium pullulans,Fusarium sp. The results of this study demonstrate that the reason of declining of stone fruit trees in Moravia is caused probably by trunk pathogens.